MENGIDENTIFIKASI OPINION LEADERS DALAM MENENTUKAN PILIHAN TERHADAP SUATU PERGURUAN TINGGI - Howard S. Giam; Danny Santoso (Business Management Journal, 2017)
The topic of this article is about buying decision. There are many issues that can be discussed in buying decision, such as stages of buying decision process, factors that inluence buying decision, and opinion leaders who persuade in making a buying decision. However, the article only focuses on the opinion leaders, especially in choosing a higher education. It explores the influencers of high school students in taking up a higher education as a place to study, both from quantitative and qualitative perspectives.  Key Words: Buying decision, opinion leader.